Disparities in Emergent Colectomy for Colorectal Cancer Contribute to Inequalities in Postoperative Morbidity and Mortality in The US Health Care System. (June 2020) - Schlottmann, F.; Strassle, P. D.; Cairns, A. L.; Herbella, F. A. M.; Fichera, A.; Patti, M. G.
Background and Aims: Colorectal cancer is the third most common cancer among both men and women in the United States. We aimed to determine racial and socioeconomic disparities in emergent colectomy rates for colorectal cancer in the US Health Care system. Material and Methods: We performed a retrospective analysis of the National Inpatient Sample including adult patients (⩾18 years) diagnosed with colorectal cancer, and who underwent colorectal resection while admitted between 2008 and 2015. Multivariable logistic and linear regression were used to assess the association between emergent admissions, compared to elective admissions, and postoperative outcomes. Results: A total of 141, 641 hospitalizations were included: 93, 775 (66%) were elective admissions and 47, 866 (34%) were emergent admissions. Black patients were more likely to undergo emergent colectomy, compared to white patients (42% vs 32%, p < 0.0001). Medicaid and Medicare patients were also more likely to have an emergent colectomy, compared to private insurance (47% and 36% vs 25%, respectively, p < 0.0001), as were patients with low household income, compared to highest (38% vs 31%, p < 0.0001). Emergent procedures were less likely to be laparoscopic (19% vs 38%, p < 0.0001). Patients undergoing emergent colectomy were significantly more likely to have postoperative venous thromboembolism, wound complications, infection, bleeding, cardiac failure, renal failure, respiratory failure, shock, and inpatient mortality. Conclusion: There are significant racial and socioeconomic disparities in emergent colectomy rates for colorectal cancer. Efforts to reduce this disparity in colorectal cancer surgery patients should be prioritized to improve outcomes.